(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The purpose of this study is to provide precise quantitative data for the lattice parameter as a function of silicon concentration, which can be used as a means of determining composition of samples. The results of lattice parameter measurements on the series ferrite over the range are reported. The lattice constants were calculated by two ways: first, as average and second, in terms of diffractometer extrapolation function. The single phase spinel structure of the sample was confirmed by X – ray diffraction technique. We found that the lattice constant decreases as x increasing. In addition, we calculated the cation – cation distance dc-c in the tetrahedral and octahedral sites. تهدف هذه الدراسة إلى تقديم بيانات كمية دقيقة عن بارامتر الشبكة بتابعية تركيز السليكون والتي يمكن أن تستخدم كوسيلة لتحديد تركيب العينات المدروسة. في هذا العمل سجّلت نتائج قياسات بارامتر الشبكة لسلسلة من عينات فرايتية في المجال . لقد وجدنا ثابت الشبكة لكل عينة بطريقتين : أولا,كقيمة متوسطة مأخوذة من طيف كل عينة ,وثانياً بمساعدة تابع الاستقراء في الانعراج. وتم التأكد من الطور الوحيد للبنية السبينلية للعينات المدروسة باستخدام طريقة انعراج الأشعة السينية. لقد وجدنا أن ثابت الشبكة a للعينات يتناقص بزيادة تركيز السليكونx . علاوةً على ذلك, حسبنا المسافة الفاصلة dc-c بين كاتيون – كاتيون في المواقع الرباعية والثمانية في البلورات المدروسة .